2005
DOI: 10.1534/genetics.104.035139
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential-Like Channels Are Essential for Calcium Signaling and Fluid Transport in a Drosophila Epithelium

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…In the first report describing TRP␥, its expression was shown to specifically occur in Drosophila eyes and the head, but not in the body (17), suggesting a possible sensory function of TRP␥. In contrast, a second report showed that the transcription of TRP␥ mRNA not only occurs in the fruit fly's head but also in the cells of the Malpighian tubules (18). Similarly, our present RT-PCR data support the notion that TRP␥ expression is not restricted to Drosophila head.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the first report describing TRP␥, its expression was shown to specifically occur in Drosophila eyes and the head, but not in the body (17), suggesting a possible sensory function of TRP␥. In contrast, a second report showed that the transcription of TRP␥ mRNA not only occurs in the fruit fly's head but also in the cells of the Malpighian tubules (18). Similarly, our present RT-PCR data support the notion that TRP␥ expression is not restricted to Drosophila head.…”
Section: Discussionsupporting
confidence: 87%
“…Xu et al showed expression of TRP␥ predominantly in Drosophila head (17). In contrast, two recent publications showed a much broader distribution of TRP␥ (18,19). A broad expression pattern of TRP␥ and the fact that there are only three TRPC members (TRP, TRPL, TRP␥) in the genome of Drosophila make it likely that a TRP␥-mediated Ca 2ϩ influx is integrated in many receptor-mediated signaling pathways outside the visual system.…”
mentioning
confidence: 99%
“…During the course of the experiment, it was reported that TRPL was expressed not only in Drosophila eyes but also in the Malpighian tubules (29). We therefore tested whether the highly significant difference in TRPL expression was maintained if RNA from heads only was measured.…”
Section: Methodsmentioning
confidence: 99%
“…PDE1 and PDE11), so this allows for further cross-talk between cAMP and cGMP under physiological conditions. , receptor guanylate cyclase Gyc76c ] and Ca 2+ channels [L-type (MacPherson et al, 2001), transient receptor potential (TRP) and TRP-like (TRPL) (MacPherson et al, 2005) and cyclic nucleotide-gated (CNG) (Broderick et al, 2003)] on the basolateral membrane. Intracellular organelles, i.e.…”
Section: Camp Signallingmentioning
confidence: 99%